Using reflections and questioning to engage and challenge online graduate learners in education - Yuliang Liu (The Asia-Pacific Society for Computers in Education (APSCE), 2019)
Abstract This paper reports an action research that aimed to examine how the author's weekly use of reflection and questioning instructional methods affected learners' learning in an online graduate class at a midwestern public university in the USA. The author employed the asynchronous online discussion on the discussion board in Blackboard for learners to complete course assignments. Specifically, the online instructional approach started with learners' initial written reflection posts based on the assigned readings and personal experience, then followed by the instructor's challenging questions based on the Socratic method and learners' written responses to those questions. This method included discipline-specific questioning, creating a community where learners replied to the instructor's and learners' questions through modelling and facilitation, and promoting the instructor's thinking-encouraging approach. The results of both quantitative and qualitative data indicated that the use of the reflection and questioning methods was effective in engaging and challenging online graduate learners. International implications across the discipline will result from the study.